African swine fever in Gauteng province, South Africa: biosecurity risks - (:unkn) unknown (My University, 2022)
Objective(s) - The 2012 and 2016-2022, African swine fever (ASF) outbreaks in Gauteng are suspected to form part of the domestic cycle, which consists of pig-to-pig transmission. The objective of this study was to determine the potential risk of ASF spread within and to Gauteng with reference to specific areas, which are currently known to be ASF-free and areas exposed to ASF outbreaks from 2016-2022. Method and Materials - In 2020 and 2021, pig farmers willing to participate in the study had been identified. Hundred and thirty-seven farmers agreed to participate in the study, which allowed the researchers to conduct telephonically interviews (due to COVID-19 epidemic) and/or face-to-face interviews. The latter were achieved by obtaining data from smallholder farmers using questionnaires, which included questions on the general characteristics of the farm and household, herd size and ownership, pig and animal health management, biosecurity measures, pig trade and movement, awareness of ASF, sanitary measures and possible virus introduction routes. Farmers were divided according to three criteria based on their past experience toward the disease and the ASF status of the area in which they were located. Results - Data collected indicate knowledge gaps regarding ASF in general. Lack of basic biosecurity knowledge as well as application thereof such as free-roaming pigs were identified as risk factors. Results further show that there is evidence of informal movements or trade in the area. Conclusion - Creating awareness and improving of knowledge on African swine fever, biosecurity and control is an aspect required by many smallholder farmers in the Gauteng Province. Farmers still need training on some of the basic cost effective biosecurity measures they can be implement on farms.
Keywords: African Research